Job-related stressors: challenges and hindrances in innovative work - MONICA, DR. BENITA. S.; MS. NITHYASHREE K (The journal of contemporary issues in business and government, 2020)
Work Stress is one of the most demoralizing and perilous hindrance which affects the overall effectiveness of any employee. Especially in the IT industry, where the intellectual ability of employees plays a major role, work related stressors need to be identified. The objective of the study is to examine the job-related stressors experienced by employees in the IT sector. Some of the work-related stressors considered in the study are job insecurity, workload, feedback and suggestions, daily challenge in work and daily hindrance in work. The sample size of the study is 60 and respondents were IT employees. Regression analysis is used to identify the significant stressors suffered by employees. The results suggest that workload is the significant stressor of work stress. Suggestions are given to line managers to help them handle the stress experienced by their workers.